Birds Species of Rallidae Family in Forestry and Environment Research and Development Institute of Manado - Diah Irawati Dwi Arini (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2016)
This study aims to determine species and conservation status of Rallidae family in Forestry and Environment Research and Development Institute of Manado; also the prospect of its development. This study may provide a source of data and information on the diversity of certain bird species. Observations conducted in June 2015 included the species of birds in Rallidae family found around the Forestry and Environment Research and Development Institute of Manado. Data were analyzed descriptively in the forms of figures and tables. Results showed that there were three species within this family found in Manado Forestry Research Institute. Those were isabelline bush-hen (Amaurornis isabellina), buff-banded rail (Gallirallus philippensis), and Barred Rail (Gallirallus torquatus). All three species are not protected in Indonesia and IUCN categorized them as Least Concern (LC). Isabelline bush-hen is endemic to the island of Sulawesi, while buff-banded rail and barred rail have a wide distribution. Weris has a good prospect to be domesticated.